Soldiers on the Move. Legio V Macedonica’s Tile Stamps and the Deployment of Vexillations in the 2nd-4th centuries AD - NEMETI, Sorin (Studia Universitatis Babeș-Bolyai Historia, 2025)
From the 1st to the 4th century AD, various literary and epigraphic sources talk about the deployment of vexillations of the Fifth Macedonian Legion. For the history of the movements of the soldiers of the Fifth Macedonian Legion, we should combine the data from literary sources with three different epigraphic corpora: firstly, the epigraphic mentions of the vexillations of this legion in inscriptions containing the careers of some officials or officers, secondly, the data offered by votive or funerary inscriptions regarding soldiers grouped in settlements other than the garrison locations, and thirdly, the distribution of the tile and brick stamps with the abbreviated name of the legion. The history of this legion could be split into four main stages, according to the garrison locations: Oescus I (1st c. AD-106 AD), Troesmis (106-170 AD), Potaissa (170-271 AD), and Oescus II (3rd-4th c. AD). Generally, tile stamps are considered minor epigraphic sources and are often neglected by the mainstream historical discourse. In spite of their minor importance, their chronological value and their distribution, the preference for certain types of stamps in each of the garrison sites and in each historical era, allow the tracing of the collective movements of soldiers in connection with the campaigns of the emperors or with missions in newly conquered or partially controlled territories. Rezumat: Diferite surse literare și epigrafice din secolele I-IV p. Chr. vorbesc despre deplasarea unor vexilații din legiunea V Macedonica. Pentru istoria deplasărilor soldaților legiunii V Macedonica, trebuie să combinăm datele din sursele literare cu trei corpora epigrafice distincte: în primul rând, mențiunile epigrafice ale vexilațiilor acestei legiuni în inscripții conținând carierele unor oficiali sau ofițeri, în al doilea, datele oferite de inscripțiile votive și funerare despre soldați grupați în alte așezări decât locurile de garnizoană și, în al treilea, distribuția țiglelor și cărămizilor ștampilate cu numele abreviat al legiunii. Istoria acestei legiuni poate fi împărțită în patru etape diferite, în funcție de locurile de garnizoană: Oescus I (sec. I-106 p. Chr.), Troesmis (106-170 p. Chr.), Potaissa (170-271 p. Chr.) și Oescus II (sec. III-IV p. Chr.). În general, ștampilele tegulare sunt considerate izvoare epigrafice minore și adesea sunt neglijate de discursul istoric principal. În ciuda importanței lor minore, valoarea lor cronologică și distribuția în spațiu, preferința pentru anumite tipuri de ștampile în fiecare loc de garnizoană și în fiecare epocă, permit reconstituirea deplasărilor colective ale soldaților în relație cu campaniile împăraților ori cu misiuni în teritorii nou cucerite sau doar parțial controlate. Cuvinte-cheie: Legio V Macedonica, ștampile tegulare, vexilații, epigrafie, istorie militară